Why promising technologies fail: the neglected role of user innovation during adoption - Douthwaite, Boru; Keatinge, J.D.H.; Park, J.R. (Elsevier, 2001)
The paper analyses innovation histories of two agro-mechanical and two seed-based technologies with high and low technological complexity, introduced into simple and complex farming systems in Asia. The main conclusion, which may be seen as a hypothesis for further testing, is that, as technology and system complexity increase so does the need for interaction between the originating R&D team and the key stakeholders (those who will directly gain and lose from the innovation) when the latter first replicate and use the new technology. This is because a successful technology represents a synthesis of the researcher and key stakeholder knowledge sets, and creating this synthesis requires more iteration and negotiation as complexity increases. Instead of assuming a new technology is ‘finished’ when it leaves the research institute, a more effective way of developing complex technologies is for the R&D team to release them as soon as the key stakeholders will adopt, and then nurture the technology’s continued development in partnership with the key stakeholders.